2015
DOI: 10.3390/f6124381
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Nitrogen Addition on Leaf Decomposition of Single-Species and Litter Mixture in Pinus tabulaeformis Forests

Abstract: Abstract:The litter decomposition process is closely correlated with nutrient cycling and the maintenance of soil fertility in the forest ecosystem. In particular, the intense environmental concern about atmospheric nitrogen (N) deposition requires a better understanding of its influence on the litter decomposition process. This study examines the responses of single-species litter and litter mixture decomposition processes to N addition in Chinese pine (Pinus tabulaeformis Carr.) ecosystems. Chinese pine litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Our findings stated that the initial C/N ratio in leaf and twig litters was 32 and 65, respectively. Therefore, lower initial N content and higher C/N ratio, as well as higher lignin and cellulose residues in twig litter, could be one of the main reasons for their slower decomposition rate than the leaf litter [17]. In addition, Our outcomes demonstrated that the initial P content and the ratios of litter C/P and N/P might be critical factors that affect rates of decomposition.…”
Section: Impacts Of N Addition On Nutrient Releasementioning
confidence: 69%
See 1 more Smart Citation
“…Our findings stated that the initial C/N ratio in leaf and twig litters was 32 and 65, respectively. Therefore, lower initial N content and higher C/N ratio, as well as higher lignin and cellulose residues in twig litter, could be one of the main reasons for their slower decomposition rate than the leaf litter [17]. In addition, Our outcomes demonstrated that the initial P content and the ratios of litter C/P and N/P might be critical factors that affect rates of decomposition.…”
Section: Impacts Of N Addition On Nutrient Releasementioning
confidence: 69%
“…Tie et al [3] discovered that a lower C/N ratio and litter pH in the soil was associated with the N additions, which inhibited the degradation of litter and nutrient availability in a subtropical forest. However, Wang et al [17] found no significant difference in litter composition, possibly because of the fact that the stimulatory impact of N addition on the Chinese pine litter may counteract the inhibitory action on the Mongolian oak litter in a temperate forest. The above-mentioned studies primarily discussed the effect of N additions on the decomposition of leaf litter.…”
Section: Introductionmentioning
confidence: 97%
“…In these two mixtures, non-additive effects and synergistic interactions have been reported. These findings suggest that N-rich leaf litter (A. africana) may transfer nutrients to N-poor litter (V. paradoxa), which increases the decomposition rate [8,14,30,39]. This evidence is supported by a study in northern Canada [40] that found the decomposition rate was increased only in a mixture containing N-rich speckled alder leaves, and was conversely inhibited by mixing yellow birch leaves with red maple leaves.…”
Section: Effect Of Azolla Africana On the Decomposition Of Leaf Litter Of Poor Qualitymentioning
confidence: 74%
“…Since the 1990s, P. tabulaeformis has been widely used in vegetation recovery of soil dumps in the mines in Chinaʼs Loess Plateau, and is known for its excellent coldand barren-resistant capability (Qi et al, 2020). After 30 years of growth, a small part of the P. tabulaeformis plantations is succeeded by more diversified native ecosystems (Wang et al, 2016). However, a greater proportion of the P. tabulaeformis plantations also undergo vegetation degeneration, as typified by the small, aged trees and even extensive death (Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%